Galeni In Hippocratis Epidemiarum librum II commentariorum I-VI versio Arabica. Volume I: Commentaria I-III - Vagelpohl, Uwe (Corpus Medicorum Graecorum - Supplementum Orientale, 2016)
This two-volume monograph offers the first critical edition of the medieval Arabic translation of Galen's Commentary on Book 2 of the Hippocratic Epidemics produced by Hunayn ibn Ishaq (d. ca. 870). The edition is based on all extant Arabic textual witnesses, including the Arabic secondary transmission. The Greek original of this text is lost; the Arabic translation is therefore the only witness to this important work. The number and extent of quotations from this commentary in medieval Arabic medical writings, which are documented in the introduction to the volume, demonstrate that it became a crucial source for the development of medicine in the Islamic world. It also gave rise to a wide range of didactic writings which illustrate its importance for medical teaching. The English translation that accompanies the edition aims to convey some of the flavour of the Arabic text. It also comes with comprehensive indices that map out the terminology and style of the translation.